Perceptions of undergraduate nursing students toward providing care to COVID-19 patients - Faizi, Fakhrudin; Moradian, Seyed Tayeb (Frontiers in Public Health, 2022)
Background: Undergraduate nursing students were inevitably recruited to provide care in response to overloaded hospitals with COVID-19 patients. The placement could be a stressful event and we aimed to understand the students’ perception of direct nursing care during the pandemic. Methods: The qualitative content analysis study carried out in 2020 (May-June) in Tehran, I.R. Iran. Using explanatory questions, we interviewed Fifteen undergraduate nursing students that provided direct care for at least two months to patients hospitalized with COVID-19 in the beginning of the pandemic interviewed to obtain their deep experiences. We applied the MAXQDA 10 to extract codes, qualitative content analysis method to investigation and then the Lincoln and Guba criteria for rigor and trustworthiness. The study was approved by National Committee for Ethics in Biomedical Research (IR.BMSU.REC.1399.070. available at: https://ethics.research.ac.ir). Results: Four hundred and fifty-four codes were identified, which were then categorized into 12 categories emerging four main themes of “hard and unpredictable”, “post traumatic growth”, “on the path to self-determination”, and “commitment”. Conclusion: Even though the undergraduate nursing students experienced some stress in the beginning; however, with close support, their skills of caring improved and they developed their ability to comply with the national healthcare needs. More studies will illustrate better experiences of the nursing students in combating COVID-19. Keywords Nursing student, perception, experience, COVID-19, posttraumatic growth